Generation of two iPSC lines from vascular Ehlers-Danlos Syndrome (vEDS) patients carrying a missense mutation in COL3A1 gene - Amit Manhas; Dipti Tripathi; Chikage Noishiki; David Wu; Lu Liu; Karim Sallam; Jason T. Lee; Eri Fukaya; Nazish Sayed (Stem Cell Research, 2024)
Vascular Ehlers-Danlos Syndrome (vEDS) is an inherited connective tissue disorder caused by COL3A1 gene, mutations that encodes type III collagen, a crucial component of blood vessels. vEDS can be life-threatening as these patients can have severe internal bleeding due to arterial rupture. Here, we generated induced pluripotent stem cell (iPSC) lines from two vEDS patients carrying a missense mutation in the COL3A1 (c.226A > G, p.Asn76Asp) gene. These lines exhibited typical iPSC characteristics including morphology, expression of pluripotency markers, and could differentiate to all three germ layer. These iPSC lines can serve as valuable tools for elucidating the pathophysiology underlying vEDS.